Assessment of losses by spot blotch (Bipolaris sorokiniana) with reference to resistance in wheat in Tarai region of Uttaranchal - KANAK SRIVASTAVA* and J.P. JAISWAL, PRASHANT GOEL, SWATI, SOHAN PAL, (Indian Phytopathology, 2006)
Spot blotch caused by Bipolaris sorokiniana is gaining importance especially in North Western and North Eastern Plain Zones (NWPZ and NEPZ) of India. The experiment was conducted at Crop Research Centre, Pantnagar in Tarai region of Uttaranchal by taking three resistant i.e. WH 581, PBW 343 and PBW 373, three susceptible varieties, UP 2338, PBW 154 and Sonalika, and their F" F2, B, and B2 generations. The average yield and 1000-grain weight losses due to spot blotch were 17.63 and 19.35 per cent, respectively in different generations. The grain yield loss ranged from 7.63 to 36.66 per cent while reduction in 1000-grain weight ranged from 7.07 to 43.65 per cent. The resistance genotype(s) exhibited minimum loss in comparison to the susceptible genotype(s).